Electromyography and neuromuscular disorders : clinical-electrophysiological correlations - Preston, David C. (Elsevier Saunders, 2013)
Diagnose neuromuscular disorders more quickly and accurately with Electromyography and Neuromuscular Disorders: Clinical-Electrophysiologic Correlations, 3rd Edition! State-of-the-art guidance helps you correlate electromyographic and clinical findings and use the latest EMG techniques to their fullest potential. Successfully correlate electrodiagnostic findings with key clinical findings for more confident diagnoses. Clearly see how to apply what you've learned with abundant case studies throughout the book. Obtain relevant clinical guidance quickly and easily with an accessible, easy-to-read writing style that's both comprehensive and easy to understand.- Resumé vydavatel
Keywords: elektromyografie; neuromuskulární nemoci; diagnostika (lékařství); electromyography; neuromuscular diseases; medical diagnostics; elektronické knihy; monografie; electronic books; monographs